Perception of coordinators of Basic Health Units in Irati-PR / Brazil on the proposal for a physical activity program for the elderly (Revista Contexto & Saúde, 2025)
The aim of the study was to analyze the perceptions of the coordinators of the Basic Health Units (BHU) about a proposed physical activity program for the elderly, in the context of Primary Health Care (PHC) in Irati-PR. This is a qualitative, descriptive and explanatory study. As a research technique, we used semi-structured interviews to gather information on the coordinators' perception of the program's proposal. The data was analyzed through content analysis, using the categorical analysis technique. The study involved eleven participants, nine of whom were BHU coordinators, one outpatient coordinator and one PHC coordinator. The results showed that the BHU coordinators' perceptions of the proposal for a physical activity program for the elderly were: attribution of adjectives connoting approval of the proposal; insertion of the Physical Education professional and development of the program in the BHU; prospects for improvements in the physical and mental health levels of the elderly participants; potential for promoting physical activity for the elderly population in the BHU territory; dependence on the efforts of municipal management related to financial resources for the feasibility of implementing programs of this nature; lack of professionals and employees available to work in the program. Despite the positive attitudes towards the proposal, recognition of the potential and importance of programs of this nature for the health of the municipality's elderly population, the coordinators highlight aspects that deserve attention in order to enable the implementation of actions aimed at promoting healthy aging.
Keywords: Elderly; Primary Health Care; Health Promotion; Evaluation of Health Programs and Projects; Motor Activity